Factores de riesgo y su influencia en desarrollar infarto agudo de miocardio en adultos jóvenes que acuden al área de emergencia del hospital Martín Icaza del cantón Babahoyo provincia Los Ríos en el periodo octubre 2019- marzo 2020. - Contreras Contreras, Jordy Ronaldo (2020)
At present, ischemic heart disease is the leading cause of death in Ecuador, 10% occurred due to cardiac infarction, this ischemic disease tends to develop due to bad habits and different risk factors. OBJECT: To determine the risk factors that influence the development of acute myocardial infarction in young adults attending the Emergency Area of Martin Icaza Hospital. METHODOLOGY: Field study, inductive, deductive, descriptive, with a qualitative-quantitative approach. A non-probabilistic sampling was carried out according to inclusion and exclusion criteria and consisted of 70 patients. Informal and direct scientific observation techniques, surveys, were used. RESULTS: As a result of the proposal, a satisfactory number of patients and family members have been able to increase their level of knowledge about the prevention and control measures of the risk factors that can cause an AMI. CONCLUSION: That based on the data obtained using our universe or population as a study, it was determined that the risk factors are the predominant in the development of acute myocardial infarction due to the fact that a group of people were surveyed measuring both their level of knowledge on this pathology and its state of health.